Electronic diaries in the management of haemophilia gene therapy: Perspective of an expert group from the German, Austrian and Swiss Society on Thrombosis and Haemostasis (GTH). Issue 2 (19th February 2022) - Miesbach, Wolfgang; Eichler, Hermann; Holstein, Katharina; Holzhauer, Susanne; Klamroth, Robert; Knöfler, Ralf; Male, Christoph; Olivieri, Martin; Oldenburg, Johannes; Tiede, Andreas
Abstract: Introduction: Gene therapy (GT) is becoming a realistic treatment option for patients with haemophilia. Outside clinical trials, the complexity and potential complications of GT will pose unprecedented challenges to haemophilia care centres. Aim: To explore the potential use of electronic tools to improve the delivery of GT under real‐world conditions. Methods: Considering the hub‐and‐spoke model, the GTH working group on GT considered the entire patient pathway and reached consensus on requirements for an integrative software tool to secure documenting and sharing information between treaters, pharmacies and patients. Results: Six steps of the gene therapy process were identified, each requiring completion of the previous step as a prerequisite for entry. The responsibilities of GT dosing and follow‐up treatment centres, read/write access rules, and the minimum data set were outlined. Data contributed by patients through mobile devices was also considered. Conclusion: Important information needs to be shared between patients and treatment centres in a real‐world GT hub‐and‐spoke model. Collecting and sharing this information in well‐organised electronic applications will not only improve patient care but also enable national and international data collection in clinical registries.